Oxytocin Receptor Genetic Variation Promotes Human Trust Behavior - Krueger, Frank; Parasuraman, Raja; Iyengar, Vijeth; Thornburg, Matthew; Weel, Jaap; Lin, Mingkuan; Clarke, Ellen; McCabe, Kevin; Lipsky, Robert (Frontiers in Human Neuroscience, 2012)
Given that human trust behavior is heritable and intranasal administration of oxytocin enhances trust, the oxytocin receptor (OXTR) gene is an excellent candidate to investigate genetic contributions to individual variations in trust behavior. Although a single-nucleotide polymorphism involving an adenine (A)/ guanine (G) transition (rs53576) has been associated with socio-emotional phenotypes, its link to trust behavior is unclear. We combined genotyping of healthy male students with the administration of a trust game experiment. Our results show that a naturally occurring genetic variation (rs53576) in the OXTR gene is reliably associated with trust behavior rather than a general increase in trustworthy or risk behaviors. Individuals homozygous for the G allele (GG) showed higher trust behavior than individuals with A allele carriers (AA/AG). Although the molecular functionality of this polymorphism is still unknown, future research should clarify how the OXTR gene interacts with other genes and the environment in promoting socio-emotional behaviors.